Bilateral Optic Neuritis as an Atypical Presentation of Primary Sjögren’s Syndrome (pSS) - Denisa Rosati; Lukisiari Agustini (Vision Science and Eye Health Journal, 2022)
Introduction: Primary Sjögren’s syndrome (pSS) is a chronic progressive autoimmune disease that primarily affects exocrine glands with varying symptoms. Here we discuss atypical optic neuritis as an initial presentation of pSS without any sicca symptoms. Case presentation: A 22-year-old woman came to the outpatient clinic with the chief complaint of rapid deteriorating visual acuity that had started one week before—no complaint of the eye or other mucosal dryness. At the initial visit, best corrected visual acuity (BCVA) was hand movement on the right eye and 6/7.5 on the left eye with decreasing color perception. Fundus examination showed bilateral optic nerve head edema. Schirmer test and tear-film break up time were within normal limits. After the initial one gram intravenous methylprednisolone treatment, no significant changes were observed for three consecutive days. Serological investigations revealed raised levels of SS-A native. Improvement happened after being given azathioprine. Conclusion: Optic neuritis may be the initial presentation of Sjögren’s syndrome without sicca symptoms. The presence of a specific antibody, including anti-SSA, is supportive for the diagnosis of such a case.